Midwives’ Legal Authority for Ultrasonography in Obstetric Emergencies at Community Health Centers - Santosa, Budi; Prayuti, Yuyut (Research Horizon, 2025)
Indonesia’s maternal mortality ratio remains high, largely due to delayed detection of obstetric complications at primary health centres. Ultrasonography is vital for early diagnosis and referral, yet regulations prohibit midwives the primary maternal care providers from operating ultrasound machines, even in emergencies. This study analyses the legal framework, contrasts it with field practices, and compares it with international standards using normative juridical methods (statutory, comparative, and case approaches). The findings reveal a sharp conflict, regulations explicitly reserve ultrasound operation for physicians and radiologists, while midwives routinely perform basic scans out of necessity in areas without doctors, creating a legal grey area that exposes them to professional sanctions, civil claims, or criminal charges regardless of patient outcome. This uncertainty encourages defensive practice and contributes to delays that cost lives. The study concludes that continued prohibition is unsustainable. Urgent regulatory reform is needed to grant certified midwives limited, clearly defined authority to perform obstetric point-of-care ultrasound through a new specific ministerial regulation that includes national training, restricted scope, and explicit legal protection. Such reform would align law with clinical reality and international best practice, provide legal certainty for midwives, and accelerate the reduction of preventable maternal deaths in Indonesia.